Shareholder Wealth Effects of Cross-border Mergers and Acquisitions: Empirical Evidence from European Bidders - YU, BO (2014)
While cross-border mergers and acquisitions (M&As) have accelerated over time, the understanding of whether it can create or destroy shareholder wealth is limited. The relationship between firm’s legal origin and shareholder return in M&A is also worth investigating. This paper investigates the impact of cross-border M&As on shareholder return in acquiring firms and examines the effect of firm’s legal origin on shareholder wealth in a context of M&As. Further, it explores the determinants of bidders’ return in cross-border M&As, which is more complex than domestic M&As.